Comparison of optical coherence tomography findings in a patient with central retinal artery occlusion in one eye and end-stage glaucoma in the fellow eye - Greene, Daniel P. (2012)
This case describes a patient with chronic central retinal artery occlusion in one eye and end-stage traumatic glaucoma in the fellow eye. Optical coherence tomography (OCT) of the macula of the chronic phase of central retinal artery occlusion of the right eye indicated loss of the normal foveal depression, extensive inner retinal atrophy, and marked retinal thinning. In contrast, scans of the left eye with end-stage glaucoma demonstrated an intact foveal depression and limited retinal thinning. The pattern of macular OCT findings in this patient illustrates distinguishing features between chronic central retinal artery occlusion and chronic optic neuropathy due to end-stage glaucoma.